Probabilistic model for constraining the Galactic potential using tidal streams - Sanders, J (2014)
We present a generative probabilistic model for a tidal stream and demonstrate how this model is used to constrain the Galactic potential. The model takes advantage of the simple structure of a stream in angle and frequency space for the correct potential. We investigate how the method performs on full 6D mock stream data, and mock data with outliers included. As currently formulated the technique is computationally costly when applied to data with large observational errors, but we describe several modifications that promise to make the technique computationally tractable.